1999
DOI: 10.1021/ie990078s
|View full text |Cite
|
Sign up to set email alerts
|

Deactivation of Cu/ZnO/Al2O3 Methanol Synthesis Catalyst by Sintering

Abstract: The loss of Cu/ZnO/Al 2 O 3 activity for methanol synthesis has been studied over 50 h under a range of synthesis gas compositions. Experiments have been carried out at differential and finite conversions in order to compare deactivation under the pure feed to that in the presence of products. Under differential conversion, it was found that the degree of deactivation was related to the CO concentration, being particularly acute under CO/H 2 . Under CO/H 2 , there was a close correlation between activity loss … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
104
1
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(118 citation statements)
references
References 15 publications
10
104
1
1
Order By: Relevance
“…It is clear that the Cu/ZnO/Al 2 O 3 suffers from rapid deactivation under these conditions. This deactivation is not surprising and caused by sintering of the Cu particles [16]. This is in stark contrast with the trend observed for the 8.8Pd/ZnO/Al 2 O 3 -0.38 catalyst.…”
Section: Scanning Transmission Electron Microscopy Analysiscontrasting
confidence: 69%
“…It is clear that the Cu/ZnO/Al 2 O 3 suffers from rapid deactivation under these conditions. This deactivation is not surprising and caused by sintering of the Cu particles [16]. This is in stark contrast with the trend observed for the 8.8Pd/ZnO/Al 2 O 3 -0.38 catalyst.…”
Section: Scanning Transmission Electron Microscopy Analysiscontrasting
confidence: 69%
“…Previous research of our group [14] showed that as active sites of methanol synthesis, Cu 0 -Cu + was more active than Cu 0 , and there needed some oxidative atmosphere in the system to complete the cycle. Likewise, Sun et al [15] also found that Cu 0 -Cu + in methanol synthesis depressed sintering of Cu crystalline significantly.…”
Section: Comparison Of Two Regeneration Mechanismsmentioning
confidence: 87%
“…Owing to an enhanced atom mobility, low melting point metals such as Cu, Au or Ag are particularly prone to grow. Cu-based catalysts, typically promoted by ZnO, are employed in industrial processes such as the water-gas shift reaction [18,19] and the synthesis of methanol from synthesis gas [20,21], for which Cu particle growth is a prominent deactivation mechanism [22,23,24].…”
Section: Introductionmentioning
confidence: 99%